Relationship Model Based on the Value of Influence between Actors in Managing Tourism Villages - Ekasari, Astri Mutia; Rochman, Gina Puspitasari; Rakhman, Lulik Fullela (KnE Social Sciences, 2024)
Lamajang Tourism Village has enormous potential in the tourism sector which is the capital of rural development. However, it is constrained by the lack of synergetic management amongst its stakeholders. To achieve sustainable development goals, it is important to determine how the actors involved in managing Lamajang Tourism Village are related. This research aims to map the strength of the relationship and the role of influential actors in the management of the Lamajang Tourism Village. The research method uses quantitative techniques with the help of MACTOR software. Questionnaires with the scoring method are used to collect data to measure the influence of the actors involved. The study results show that the Department of Culture and Tourism is the dominant actor, meaning it plays a significant role in cooperative and collaborative efforts to advance the Lamajang Tourism Village. PKK, Gapoktan, LMDH, and community leaders have weak influence and little dependence on other actors. This finding is useful in distributing roles and duties of actors that are more directed and do not overlap according to their legitimacy and power. Keywords: MACTOR analysis, actors relationship, village tourism, actor analysis